PENGARUH PENGUNGKAPAN EMISI KARBON DAN KINERJA KEUANGAN TERHADAP REAKSI INVESTOR DENGAN KINERJA LINGKUNGAN SEBAGAI PEMODERASI: THE EFFECT OF CARBON EMISSION DISCLOSURE AND FINANCIAL PERFORMANCE ON INVESTOR REACTIONS WITH ENVIRONMENTAL PERFORMANCE AS A MODERATION - Nanda, Utari Esa; Nasir, Azwir; Nur DP, Emrinaldi (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2023)
The objective of this study is to investigate how environmental performance serves as a moderator in the association between carbon emissions disclosure (CED) and investor response. The objective of this research is to investigate the correlation between non-standard stock returns and carbon emission disclosure, utilizing environmental performance as an intermediary factor. The present analysis comprises manufacturing firms that were listed on the IDX and PROPER platforms during the period spanning from 2017 to 2020. The statistical software package SPSS version 22 was utilized to perform the hypothesis testing. The dataset comprised 27 distinct commercial entities, encompassing a cumulative count of 138 individual records. The study's sample was selected through the utilisation of purposive sampling. Multiple regression analysis is utilized in this study for the purpose of hypothesis testing. The aforementioned results indicate that the implementation of Corporate Environmental Disclosure (CED) and favorable financial performance have a constructive influence on the responses of investors. The relationship between the disclosure of carbon emissions and investor response is influenced and reinforced by environmental performance. However, the relationship between financial performance and investor response is not influenced by environmental performance.